Hoax behavior tendencies among Indonesian students: An analysis during the COVID-19 pandemic - Afdal Afdal; Miftahul Fikri; Neviyarni Neviyarni; Mega Iswari; Indah Sukmawati; Firman Firman; Yeni Karneli; Mardianto Mardianto; Rezki Hariko (Institute of Advanced Engineering and Science, 2023)
The objective of this study was to analyze the hoax behavior tendencies among Indonesian students during the pandemic, viewed from the aspects of analytical thinking, basic science knowledge, trust in news sources, satisfaction, and action. A total of 633 male and female students from Indonesian universities were sampled used a simple random sampling technique. Data were collected through the hoax tendency behavior scale (HTBS) on 30 questions using a Likert scale. Then, the data were analyzed descriptively to evaluate the hoax behavior tendencies in adolescents during the pandemic, which the results revealed to be in the medium category. Therefore, the analytical thinking skills of adolescents need to be improved, as 31.75% and 2.53% were in the low and very low categories. The study showed that adolescents with an average age of 20 years spreading hoaxes were motivated by basic knowledge of science, trust in news sources, satisfaction, and action. However, there was no significant influence of gender, parental income, and areas of residence, such as rural, urban, and suburban, on those that exhibit hoax behaviors.